Development of E-Servqual Dimensions for Banking - Emilia Sindi (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2024)
E-SERVQUAL is a tool used to measure customer service quality. This research aims to conduct a literature review on the dimensions and indicators of service quality specifically used for digital banking services. The research method has 3 stages, namely : First, Planning contains the Explanation of Research Objectives, Second, Research Identification contains the Determination of Criteria and Selection of Research Articles, Third, Selection of Basic Studies contains Selection of research articles using predetermined criteria keywords. The keyword used is "e-SERVQUAL". There are 2 selection criteria, namely the exclusion criteria, which include : Research journals cannot be downloaded, Research journals are not full text, Research journals that use e-SERVQUAL are not in the banking sector and Inclusion criteria are, Research articles that answer research questions, Research articles identified using keywords. The results of this study are : e-SERVQUAL dimensions specifically for the quality of banking services are Efficiency, Reliability, Responsiveness, Personal needs, Site organization, Fulfilment, Security/trust, Ease of use and Privacy. Not all journals regarding banking e-SERVQUAL include indicators and dimensions. Of the 10 journals studied, only 3 journals produced a significant positive value between the e-SERVQUAL variable and e-Customer Satisfaction.